Initial Pediatric Burn Management: A Practical Guide - Palmieri, Tina L. (Seminars in Plastic Surgery, 2024)
Children have an imperative to explore their environment to grow and develop, which puts them at risk for sustaining burn injury. Burn injury remains the third leading cause of injury-related death worldwide. Plastic surgeons, as experts in the evaluation and management of cutaneous injuries, are frequently called upon to evaluate and treat children with burn injuries. This article focuses on the unique physiologic aspects of children and how they impact initial evaluation and management of burn injury. Children are not “little adults,” and they have different airway, circulatory, and cutaneous systems. Understanding the signs of potential child abuse is important to avoid further child harm. Finally, recognition of the criteria for referral to a pediatric burn center is important to optimize both short- and long-term outcomes for patients and families.
Keywords: pediatrics; burn injury; initial management